Sarnevo, Bulgarien: Neolithische Tells in Nordthrakien - Komp, Rainer (e-Forschungsberichte des DAI, 2023)
The German Archaeological Institute was conducting geomagnetical surveys using a large scale magnetometry system in the area of Sarnevo, Bulgaria in the years 2014 and 2015. During the construction of the so called Thracian Motorway the site became recently known for neolithic ritual places and tell settlements. The investigation successfully resulted in images showing dwellings on tells and satellite settlements surrounded by circled earthworks. The typical diameter of the enclosures is about 130 m. Casually recorded geological features add information to the reconstruction of ancient landscapes. Further, destruction of archaeological objects by recent unsupervised interventions become obvious.